Barriers and facilitators to influenza and pneumococcal vaccine hesitancy in rheumatoid arthritis: a qualitative study. (4th June 2021) - Colmegna, Inés; Valerio, Valeria; Gosselin-Boucher, Vincent; Lacoste, Guillaume; Labbe, Sara; Lavoie, Kim L; Hazel, Elizabeth; Ward, Brian; Hudson, Marie; Peláez, Sandra
Abstract: Objectives: Immunization is an essential component of RA care. Nevertheless, vaccine coverage in RA is suboptimal. Contextual, individual and vaccine-related factors influence vaccine acceptance. However, barriers and facilitators of vaccination in RA are not well defined. The aim of this study was to assess perspectives of RA patients and healthcare professionals (HCPs) involved in RA care of barriers and facilitators regarding influenza and pneumococcal vaccines. Methods: Eight focus groups (four with RA patients and four with HCPs) and eight semi-structured open-ended individual interviews with vaccine-hesitant RA patients were conducted. Data were audio recorded, transcribed verbatim and imported to MAXQDA software. Analysis using the framework of vaccine hesitancy proposed by the Strategic Advisory Group of Experts on Immunization was conducted. Results: RA patients and HCPs reported common and specific barriers and facilitators to influenza vaccination that included contextual, individual and/or group and vaccine- and/or vaccination-specific factors. A key contextual influence on vaccination was patients' perception of the media, pharmaceutical industry, authorities, scientists and the medical community at large. Among the individual-related influences, experiences with vaccination, knowledge/awareness and beliefs about health and disease prevention were considered to impact vaccine acceptance. Vaccine-related factors including concerns about vaccine side effects such as RA flares, the safety of new formulations, the mechanism of action, access to vaccines and costs associated with vaccination were identified as actionable barriers. Conclusion: Acknowledging RA patients' perceived barriers to influenza and pneumococcal vaccination and implementing specific strategies to address them might increase vaccination coverage in this population.